2015
DOI: 10.1002/ange.201410948
|View full text |Cite
|
Sign up to set email alerts
|

A Copper(I)–Arene Complex With an Unsupported η6 Interaction

Abstract: Addition of PR 3 (R = Ph or OPh) to [Cu(h 2 -Me 6 C 6 ) 2 ][PF 6 ] results in the formation of [(h 6 -Me 6 C 6 )Cu-(PR 3 )][PF 6 ], the first copper-arene complexes to feature an unsupported h 6 arene interaction. A DFT analysis reveals that the preference for the h 6 binding mode is enforced by the steric clash between the methyl groups of the arene ligand and the phenyl rings of the phosphine co-ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The Cu–C benzene bond distances range from 2.342(9) to 2.477(8) Å, with an average of 2.404 Å, which is longer than those reported for [Cu(η 6 -C 6 Me 6 )] + . 6 Similarly, the distance between the Cu atom and the centroid of the benzene ring (Cu–C centroid 1.960 Å) in 3 is slightly longer than those in Hayton's [Cu(η 6 -C 6 Me 6 )] + complexes (1.800(3) and 1.775(6) Å), 6 but significantly shorter than those reported for the tethered Cu(arene) complexes such as Cu( i )-cyclophanes or 9,10-anthracene derived endo-cyclic Cu( i ) complexes (∼2.5–3.0 Å). 4 The [SbF 6 ] anion in the asymmetric unit shows no significant bonding interaction with the Cu + atom and the closest approach between the F atom and the Cu center (Cu···F) is 4.96(1) Å, which rules out any possibility of interaction between them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cu–C benzene bond distances range from 2.342(9) to 2.477(8) Å, with an average of 2.404 Å, which is longer than those reported for [Cu(η 6 -C 6 Me 6 )] + . 6 Similarly, the distance between the Cu atom and the centroid of the benzene ring (Cu–C centroid 1.960 Å) in 3 is slightly longer than those in Hayton's [Cu(η 6 -C 6 Me 6 )] + complexes (1.800(3) and 1.775(6) Å), 6 but significantly shorter than those reported for the tethered Cu(arene) complexes such as Cu( i )-cyclophanes or 9,10-anthracene derived endo-cyclic Cu( i ) complexes (∼2.5–3.0 Å). 4 The [SbF 6 ] anion in the asymmetric unit shows no significant bonding interaction with the Cu + atom and the closest approach between the F atom and the Cu center (Cu···F) is 4.96(1) Å, which rules out any possibility of interaction between them.…”
Section: Resultsmentioning
confidence: 99%
“…A major breakthrough in this research was recently achieved by Hayton and coworkers, who isolated two half sandwich complexes [(η 6 -C 6 Me 6 )Cu(PR 3 )][PF 6 ] (R = Ph, OPh) where the C 6 Me 6 ring is bound to the Cu ion in the η 6 coordination mode. 6 However, they have also theoretically shown that when benzene is employed instead of hexamethylbenzene as an arene, the η 2 mode is preferred, and hence surmised that the preference for the η 6 mode over the η 2 mode is exclusively due to steric repulsion between Me groups and PR 3 units. Additionally, they calculated the relative energies for [Cu(C 6 H 6 )] + in gas as well as condensed phases and found the preference for the η 2 mode in both phases but more in the condensed phase, as previously predicted by Guo et al These studies consequently lead to the question: is it even possible to isolate [Cu(η 6 -C 6 H 6 )] + in the condensed phase?…”
Section: Introductionmentioning
confidence: 99%